Effects of Ni-P + DLC multilayer coating on cavitation erosion behavior of AlSi10Mg produced by laser powder bed fusion (Fracture and Structural Integrity, 2026)
Additive manufacturing (AM) technologies are currently contributing to significant progress in the design of lightweight metal components. Al alloys constitute the most studied light metal, particularly the Al-Si ones, due to their high specific properties. However, surface-driven damage mechanisms represent a limitation in the lifespan of such components.In the present work, different coatings are studied to enhance the cavitation erosion resistance of AlSi10Mg alloy manufactured via laser powder bed fusion (L-PBF). In detail, a Ni-P single layer and a Ni-P + DLC (diamond like carbon) multilayer were considered. Erosion resistance was examined by means of ultrasonic cavitation erosion tests with periodic interruptions to monitor mass loss and damage evolution. The damaged surfaces were inspected through a field emission scanning electron microscopy (FEG-SEM) to determine the damage mechanism, with the aim of evaluating the performances of the different proposed coatings.
Keywords: L-PBF; AlSi10Mg; hydrogenated amorphous carbon (a-C:H) DLC coating; electroless Ni-P coating; cavitation erosion